PENGARUH PEMBERIAN EKSTRAK METANOL-AIR DAUN Macaranga tanarius L. TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA TIKUS YANG TERBEBANI GLUKOSA - Martina Tri Handayani; Phebe Hendra (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2013)
Abstract: This research aim to find out the effect of M. tanarius leaf methanol-water extract(MTME) whether it can lowering blood glucose levels. This research was experimental studywith one way-complete-random design using 25 male rats which divided into five groups. Therats in group I were given CMC 1% (negative control). The group II rats were given 0.45 g/kg BWdose of Glibenclamide (positive control). In group III, IV and V, the rats were given 0.43; 1.28;3.84 g/kg BW doses of MTME orally. The hypoglycemic effect of MTME was tested by using theOral Glucose Tolerance Test (OGTT) method. The blood-glucose contents were measured at the0, 15, 30, 60, 90, 180, and 240 after the OGTT and treatment. The AUC were statisticallyanalyzed using one way ANOVA and Scheffe test with 95 % convidence level. The result show thatMTME at dose 0.43; 1.28; and 3.84 g/kg BW was effective in improving oral glucose tolerance.Keywords : Blood glucose, Methanol-water extract, Macaranga tanarius